Formulating a strategy for the Northern Oil Company(Case Study) - Marei al-gburi, Muayad Hassan; Karim al-Kubaisi, Salah al-Din Awwad (Journal of Economics and Administrative Sciences, 2021)
The research aims to present a proposed strategy for the North Oil Company, and the proposed strategy took into account the surrounding environmental conditions and adopted in its formulation on the basis and scientific steps that are comprehensive and realistic, as it covered the main activities of the company (production and exploration activities, refining and refining activities, export and transport of oil, research and development activity, financial activity, information technology, human resources) and the (David) model has been adopted in the environmental analysis of the factors that have been diagnosed according to a thoughtful basis and with the participation of the company’s experts and departments and after conducting a complete survey to explore the internal and external factors And build a swot matrix by assigning weight and significance to each factor. The Bryson model was also adopted in identifying strategic issues, and it is a suitable model for profit-seeking government institutions, and after analyzing internal and external factors (EFE, IFE), it emerged that the most appropriate strategy for the company is the growth and expansion strategy (strength - opportunities SO), and this strategy provides a good opportunity To achieve the company’s goals for the next five years, and enhance the process of formulating sensitive strategic issues that are at the heart of the trend towards developing the company’s work, as it included strategic issues, obstacles, time horizons, programs and procedures, and determining the entity of implementation and follow-up with evaluation criteria. The two researchers recommended the necessity of adopting this proposed strategic document, especially as it simulates the reality of the company and responds to the requirements of its role in supporting the national economy